Pengembangan Konsep Dan Kebijakan Zero Pengangguran Lulusan di SMK ATM Majalengka - Mursidin (CV. Biha Cendekia, 2025)
Unemployment among vocational high school graduates remains a critical issue in Indonesia’s human resource development, particularly in regional areas. This condition reflects a mismatch between graduate competencies and the needs of industry. This community service program aims to develop the concept and policy of zero unemployment for graduates at SMK ATM Majalengka through an institutional policy approach, strengthening industry partnerships, and optimizing the role of the Special Job Fair Unit. The implementation method was participatory, including needs analysis, policy formulation, implementation assistance, job readiness training, and program evaluation. The results indicate an improvement in graduate job readiness, the establishment of a zero-unemployment policy document, and an increased absorption of graduates into industry and entrepreneurship. This program also produced a model for an integrated and sustainable vocational school graduate management policy. This community service activity significantly contributes to reducing the unemployment rate among vocational school graduates and can be replicated in other vocational schools with similar characteristics.